Resource Repositories and linking resources: An exploratory study (Journal of the Digital Humanities Association of Southern Africa, 2023)
In this article the existence, use and importance of repositories are explored. An introduction into language resources (LRs) is given as well as a discussion of two platforms for the distribution of language resources, namely, the repository of the South African Centre for Digital Language Resources (SADiLaR) and Lanfrica, a site that links resources. In this article, types of repositories, such as institutional and language resource repositories, will be distinguished and compared. Language preservation is proposed as an important aspect which can be strengthened by the presence and use of repositories. The view expressed in this article is that the availability of language resources and repositories are pivotal for the development, preservation and advancement of languages.Having a host site that links available resources and a repository where resources could be uploaded is a positive attribute of the mentioned online platforms, however as it will be discussed, the fact that information is available online is not a guarantee that the resources are or will be used by researchers or other interested persons, especially if they are not aware of their existence.The article is concluded with suggestions for future work, for example measuring the influence of inaccurate metadata of language resources on linguistic research.
Keywords: language resources; language preservation; repositories; under-resourced languages; data